Explorating and Reconstructing the Indegeneus Knowledge of Coffee Processing in Kerinci as a Learning Resources - Jufrida Jufrida; Wawan Kurniawan; Fibrika Rahmat Basuki; Vetty Milyani (STKIP Singkawang, 2023)
This research aims to exploring and reconstructing of indigenous knowledge of coffee processing in Kerinci into scientific knowledge. This research was qualitative using ethnoscience approach. The research was carried out at Coffee Nur Kerinci. The key informan were the owner and employees of Coffee Nur. Data collection was carried out through observation and deep interview. Qualitative data were analyzed descriptively using the Miles and Huberman models. The processing of Coffee Nur Kerinci carried out traditionally using simple tools. It consists of drying of coffee beans, roasting, cooling, pulverization, sifting, and packaging of coffee powder. Drying of coffee beans was carried out by the sun for 21 days with an average of five hours/day. The roasting process was carried out by using a roaster made of a drum that rotated on the stove. The pulverization was carried out by using a waterwheel as a driving force which was connected to eight pestles. Scientifically, the processing of Coffee Nur Kerinci can be reconstructed into scientific concepts regarding the classification of living things, heat and transfer, circular motion, collisions, and forces.